Progress of Research on the Regulatory Pathway of the Plant Shade-Avoidance Syndrome - Wang, Xiaoyan; Gao, Xinqiang; Liu, Yuling; Fan, Shuli; Ma, Qifeng (Frontiers in Plant Science, 2020)
When subject to vegetational shading, shade-avoiding plants detect neighbors by perceiving reduced light quantity and altered light quality. The former includes decreases in the ratio of red to far-red wavelengths (low R:FR) and low blue light ratio (LBL) predominantly detected by phytochromes and cryptochromes, respectively. By integrating multiple signals, plants generate a suite of responses, such as elongation of a variety of organs, accelerated flowering, and reduced branching, which are collectively termed the shade-avoidance syndrome (SAS). To trigger the SAS, interactions between photoreceptors and phytochrome-interacting factors are the general switch for activation of downstream signaling pathways. A number of transcription factor families and phytohormones, especially auxin, gibberellins, ethylene, and brassinosteroids, are involved in the SAS processes. In this review, shade signals, the major photoreceptors involved, and the phenotypic characteristics of the shade-intolerant plant Arabidopsis thaliana are described in detail. In addition, integration of the signaling mechanisms that link photoreceptors with multiple hormone signaling pathways is presented and future research directions are discussed.